2016
DOI: 10.1007/s10964-016-0501-7
|View full text |Cite
|
Sign up to set email alerts
|

Gay-Straight Alliances are Associated with Lower Levels of School-Based Victimization of LGBTQ+ Youth: A Systematic Review and Meta-analysis

Abstract: Gay-straight alliances (GSAs) are school-based organizations for lesbian, gay, bisexual, transgender, and queer (LGBTQ+) youth and their allies that often attempt to improve school climate for sexual and gender minority youth. This meta-analysis evaluates the association between school GSA presence and youth's self-reports of school-based victimization by quantitatively synthesizing 15 primary studies with 62,923 participants. Findings indicate GSA presence is associated with significantly lower levels of yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
128
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(141 citation statements)
references
References 43 publications
9
128
2
2
Order By: Relevance
“…These studies identified attributes of school environments that minimize victimization risk and increase feelings of safety at school for LGBTQ students. Positive attributes of school environments include the presence of antibullying policies that specifically include and protect LGBTQ students; supportive adults, particularly teachers and staff who have been trained to intervene effectively; student gay-straight alliances; and inclusive curricula (e.g., Kosciw, Bartkiewicz, & Greytak, 2012;Kull, Kosciw, & Greytak, 2015;Marx & Kettrey, 2016;Olsen et al, 2014;Russell et al, 2010). One logical extension is that the same school environment attributes that reduce the risk for bullying might also minimize the negative effects of bullying if LGBTQ students are bullied.…”
Section: Discussionmentioning
confidence: 99%
“…These studies identified attributes of school environments that minimize victimization risk and increase feelings of safety at school for LGBTQ students. Positive attributes of school environments include the presence of antibullying policies that specifically include and protect LGBTQ students; supportive adults, particularly teachers and staff who have been trained to intervene effectively; student gay-straight alliances; and inclusive curricula (e.g., Kosciw, Bartkiewicz, & Greytak, 2012;Kull, Kosciw, & Greytak, 2015;Marx & Kettrey, 2016;Olsen et al, 2014;Russell et al, 2010). One logical extension is that the same school environment attributes that reduce the risk for bullying might also minimize the negative effects of bullying if LGBTQ students are bullied.…”
Section: Discussionmentioning
confidence: 99%
“…It looks like the exposure to a previous stressful situation during childhood increases the risk of further exposures to other stressful or traumatic experiences, up to 80% or even beyond [3]. Great part of the evidence states that bullying in a gender dysphoria minor, is more frequent and is more often associated with psychosocial aspects compromised in adult life, compared with the general population [6,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, as mentioned before, both bullying and cyberbullying are widespread problems throughout schools and teaching centers, and a well-known issue as well as an investigative topic [5]. Bullying, in its different variants, threatens health and psychosocial development of the minor [6]. This kind of intimidation is equivalent to a subtype of aggressive behavior, where the offenders intentionally and continuously attack their victims, who are usually impotent, during a long period of time [7].…”
Section: Introductionmentioning
confidence: 99%
“…While numerous cross-sectional studies have documented benefits associated with attending high schools that have GSAs (for a review, see Marx & Kettrey, 2016), the results of Ioverno and colleagues (2016) revealed that the presence of (but not participation in) a GSA within a school was associated with experiencing less homophobic victimization at follow-up (9-13 months). However, both the presence of and participation in a GSA were associated with greater perceptions of school safety at follow-up.…”
Section: Introduction To the Special Sectionmentioning
confidence: 97%